Motivation and stimulation of civil servants – participants in project activities - Yu. N. Shedko (Вестник университета)
An experience of material and non-material stimulation of participants of project activity in executive authorities abroad has been examined. Possibilities of adaptation of methods and tools of material and non-material stimulation in Russia have been established. It has been recommended to increase the quality of formal personnel procedures and to use the criterion of «personal eff ctiveness», when paying for civil servants employed in project management. The obtained results will allow adjusting the current approach to material and non-material incentives for project activity participants in the executive authorities of the Russian Federation.